Dynamic utility-based buffer management strategy for delay-tolerant networks. (2019) - Ababou, Mohamed; Kouch, Rachid El; Bellafkih, Mostafa
Delay tolerant network (DTN) is a new networking concept characterised by intermittent connections between nodes communicating through the store-carry-and-forward mechanism. Indeed, the nodes may keep a message in their buffer for long periods of time until a communication opportunity occurs and then transmit it to other relays or to its final destination. Accordingly, the use of many messages can induce buffer congestion of some nodes due to the limited buffer capacity. To manage properly the use of network resources, particularly bandwidth and buffer space of nodes, we propose, in this paper, a new buffer management strategy that consists of messages scheduling and dropping policies on the basis of a multi-criteria utility function. The simulations results under the ONE simulator have shown that the proposed buffer management strategy achieves a higher delivery ratio, reduces the average delivery delay and generates minimal overhead when compared to the Random, MOFO and FIFO usual strategies.